Angle droop versus frequency droop in a voltage source converter based autonomous microgrid - Majumder, R.; Ghosh, Arindam; Ledwich, G.; zare, F. (Institute of Electrical and Electronics Engineers ( IEEE ), 2009)
This paper compares the performance of angle and frequency droops in an autonomous microgrid that only contains voltage source converter (VSC) interfaced distributed generators (DGs). As a VSC can instantaneously change output voltage waveform, power sharing in a microgrid is possible by controlling the output voltage angle of the DGs through droop. The angle droop is able to provide proper load sharing among the DGs without a significant steady state frequency drop in the system. It is shown that the frequency variation with the frequency droop controller is significantly higher than that with the angle droop controller. The angle droop controller is derived from DC load flow. Both the angle and frequency droop controllers are designed through eigenvalue analysis. The performance of these two controllers is then performed through PSCAD simulations.